Regulation of multiple off-axis acoustic vortices with a centered quasi-plane wave - Li, Yuzhi; Li, Wen; Ma, Qingyu; Guo, Gepu; Tu, Juan; Zhang, Dong (Journal of applied physics, 2018)
In treating a circular point-source array using the phase-coded method, a composite acoustic field of multiple off-axis acoustic vortices (AVs) with a centered quasi-plane wave is proposed which is superimposed by an AV beam and a co-axial non-AV beam generated by the even- and odd-numbered source arrays, respectively. The acoustic pressure and the phase of the composite acoustic field are derived using explicit formulae and demonstrated by numerical simulations. Off-axis sub-AVs (SAVs) are shown to be formed at the intersections of the radial pressure distributions of the AV and non-AV beams for the same pressure amplitude and opposite phases. Off-axis SAVs can be generated on a circumference centered with a regular polygon of quasi-plane waves. The radii and azimuthal angles of the off-axis AVs and the radius of the centered quasi-plane wave are determined by the topological charge and the initial phase difference of the acoustic beams. With the established 16-source experimental system, the generation of multiple off-axis SAVs with a centered quasi-plane wave is demonstrated by scanning measurements of the composite field with a topological charge of 1, 2, or 3, which is also proved by the qualitatively consistent simulations for N = 16. The proposed model may be applied to multi-point vortex trapping with homogeneous particle dispersion within a finite area around the central axis. These favorable results provide the feasibility of controllable manipulation for drug particles or cells and suggest wide potential applications in the fields of sonochemistry and biomedical engineering.